The Challenges of Military Veterans in Their Transition to the Workplace: A Call for Integrating Basic and Applied Psychological Science. (May 2021) - Shepherd, Steven; Sherman, David K.; MacLean, Alair; Kay, Aaron C.
Long-standing structural features of the military have created a culture and society that is dramatically different and disconnected from civilian society. Thus, veterans transitioning to civilian society face a number of challenges related to fulfilling basic psychological needs (e.g., need for structure and order, belonging) and civilians' reliance on stereotypes to understand military veterans. In an attempt to enrich the understanding of these challenges, we integrate social psychological theories and insights with research from sociology, clinical psychology, military psychology, and organizational behavior. Theories of compensatory control, stereotype threat, and stereotyping are drawn on to help explain the psychological challenges that veterans may encounter during their transition to civilian society. We present recent research that leverages these theories to understand issues veterans face. This theoretical integration illustrates the opportunity and potential for psychological researchers to conduct basic and applied research in the context of veterans and for clinicians and managers to draw on basic theory to inform programs and interventions.